Anthropometric measures of obesity and associated cardiovascular disease risk in the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study - Saria Hassan; Carol Oladele; Deron Galusha; Oswald Peter Adams; Rohan G. Maharaj; Cruz M. Nazario; Maxine Nunez; Marcella Nunez-Smith; on behalf of the ECHORN Writing Group (BMC, 2021)
Abstract Background Accurately defining obesity using anthropometric measures that best capture obesity-related risk is important for identifying high risk groups for intervention. The purpose of this study is to compare the association of different anthropometric measures of obesity with 10-year cardiovascular disease (CVD) risk in adults in the Eastern Caribbean. Methods Data from the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study (ECS) were analyzed. The ECS is comprised of adults aged 40 and older residing in the US Virgin Islands, Puerto Rico, Barbados, and Trinidad. 10-year CVD risk was calculated using the American Heart Association (ACC/AHA) ASCVD Risk Algorithm and categorized in the following high-risk groups: > 7.5, > 10, and > 20%. Logistic regression was used to examine associations between four anthropometric measures of obesity (BMI, waist circumference, waist-to-hip ratio, waist-to height ratio) and 10-year CVD risk. Results Mean age (SD) of participants (n = 1617) was 56.6 years (±10.2), 64% were women, 74% were overweight/obese, and 24% had an ASCVD risk score above 10%. Elevated body mass index (BMI, > 30 kg/m2) and waist circumference were not associated with CVD risk. Elevated waist-to-hip ratio (WHR, > 0.9 men, > 0.85 women) and elevated waist-to-height ratio (> 0.5) were associated with all three categories of CVD risk. Area under the receiver curve was highest for WHR for each category of CVD risk. Elevated WHR demonstrated odds of 2.39, 2.58, and 3.32 (p < 0.0001) for CVD risk of > 7.5, > 10 and > 20% respectively. Conclusion Findings suggest that WHR is a better indicator than BMI of obesity-related CVD risk and should be used to target adults in the Caribbean, and of Caribbean-descent, for interventions.